The Earthquake Network Project: A Platform for Earthquake Early Warning, Rapid Impact Assessment, and Search and Rescue - Finazzi, Francesco (Frontiers in Earth Science, 2020)
Earthquake Network is a citizen science research project implementing an earthquake early warning system based on smartphone crowdsourcing. People join the project by installing a smartphone application and they receive real time alerts when earthquakes are detected by the smartphone network. Started at the end of 2012, the project has involved more than 5.5 million people and the application currently has around 500'000 active users. This makes Earthquake Network one of the largest citizen science project and an earthquake early warning system operational at the global scale. This paper aims at describing the main features of the project, of the smartphone application and of the data which are made available when an earthquake is detected in real time or reported by the application users.